A new generation of 99.999% enriched 28Si single crystals for the determination of Avogadro's constant. (24th July 2017) - Abrosimov, N V; Aref'ev, D G; Becker, P; Bettin, H; Bulanov, A D; Churbanov, M F; Filimonov, S V; Gavva, V A; Godisov, O N; Gusev, A V; Kotereva, T V; Nietzold, D; et al.
Abstract: A metrological challenge is currently underway to replace the present definition of the kilogram. One prerequisite for this is that the Avogadro constant, N A, which defines the number of atoms in a mole, needs to be determined with a relative uncertainty of better than 2  ×  10 −8 . The method applied in this case is based on the x-ray crystal density experiment using silicon crystals. The first attempt, in which silicon of natural isotopic composition was used, failed. The solution chosen subsequently was the usage of silicon highly enriched in 28 Si from Russia. First, this paper reviews previous efforts from the very first beginnings to an international collaboration with the goal of producing a 28 Si single crystal with a mass of 5 kg, an enrichment greater than 0.9999 and of sufficient chemical purity. Then the paper describes the activities of a follow-up project, conducted by PTB, to produce a new generation of highly enriched silicon in order to demonstrate the quasi-industrial and reliable production of more than 12 kg of the 28 Si material with enrichments of five nines. The intention of this project is also to show the availability of 28 Si single crystals as a guarantee for the future realisation of the redefined kilogram.